Analgesia Nociception Index: assessment of acute postoperative pain - ABDULLAYEV, RUSLAN (ELSEVIER SCIENCE INC, 2019)
Background and objectives: Patient self-rating based scales such as Numerical Rating Scale, Visual Analog Scale that is used for postoperative pain assessment may be problematic in geriatric or critically ill patients with communication problems. A method capable of the assessment of pain in objective manner has been searched for years. Analgesia nociception index, which is based on electrocardiographic data reflecting parasympathetic activity, has been proposed for this. In this study we aimed to investigate the effectiveness of analgesia nociception index as a tool for acute postoperative pain assessment. Our hypothesis was that analgesia nociception index may have good correlation with Numerical Rating Scale values. Methods: A total of 120 patients of American Society of Anesthesiologists (ASA) physical status I and II undergoing any surgical procedure under halogenated-based anesthesia with fentanyl or remifentanil were enrolled for the study. At the 15th minute of arrival to the Postoperative Care Unit the patients' pain was rated on a 0-10 point Numerical Rating Scale. The patients' heart rate, blood pressure, and analgesia nociception index scores were simultaneously measured at that time. The correlation between analgesia nociception index, heart rate, blood pressure and Numerical Rating Scale was examined. Results: The study was completed with 107 patients, of which 46 were males (43%). Mean (SD) analgesia nociception index values were significantly higher in patients with initial Numerical Rating Scale < 3, compared with Numerical Rating Scale <= 3 (69.1 [13.4] vs. 58.1 [12.9] respectively, p <0.001). A significant negative linear relationship (r2 = -0.312, p= 0.001) was observed between analgesia nociception index and Numerical Rating Scale. Conclusion: Analgesia nociception index measurements at postoperative period after volatile agent and opioid-based anesthesia correlate well with subjective Numerical Rating Scale scores. (C) 2019 Sociedade Brasileira de Anestesiologia. Published by Elsevier Editora Ltda.
Keywords: Analgesia/nociception index; Postoperative pain; Pain assessment; SURGICAL STRESS INDEX; SKIN-CONDUCTANCE; ANALGESIA/NOCICEPTION INDEX; PARAMETER